Determination of heavy metals (Lead and Cadmium) in lettuce (Lactuca sativa) in markets of Metropolitan Lima - García, Mesías M. (2019)
A study was carried out in Lima Metropolitana city to determine concentrations of lead (Pb) and cadmium (Cd) in lettuce (Lactuca sativa L.), “crespa” variety. The sampling points were 20 markets located in the North Cone, Center and South-ern Cone of Lima, which were chosen at random, 5 markets of the Northern Cone (Stone Bridge, Comas, San Martin de Porres, Los Olivos, Independencia), 10 markets of the Center (Rímac, La Victoria, Cercado de Lima, Breña, Jesús María, Barranco, Lince, Magdalena, Pueblo Libre, San Miguel) and 5 markets of the Southern Cone (Chorrillos, San Juan de Miraflores, Villa Maria del Triunfo, Villa El Salvador, Lurín), 2 samples were taken per district, making a total of 40 samples, during the recollection, in each market was questioned the origin place of the vegetable. The analytical method used for the quantification of these metals was the atomic absorption.The concentrations in lettuce showed an average of 1.279 ppm, for Pb and 0.084ppm for Cd; the Pb concentration , unlike Cd; exceeds the Maximum Level established by the WHO / FAO (Codex Alimentarius, Pb = 0.3 ppm, Cd = 0.2 ppm). In general, the lettuces of Sierra accumulate higher levels of Pb and Cd than those of the Coast. These results evidence the exposure to heavy metals in vegetables and therefore their presence in our daily diet.